RICE PROCUREMENT POLICY DURING THE SBY-BOEDIONO ADMINISTRATION - Rakib, Wahyudi; Aqmarina, Yusria; Sinaga, Randa Putra Kasea (Talenta Publisher, 2022)
This study is explored about rice procurement during the SBY-Boediono administration in Indonesia. The focus discusses what caused the SBY-Boediono government to issue a rice procurement policy. The findings of this study include, among other things, three important reasons for the government to issue this policy. First, the prevalence of land conversion in Indonesia; Second, the minimal role of Bulog in absorbing rice from peasants; Third, the phenomenon of rice imports every year. The method used is the descriptive method